Clinical presentation of gastrointestinal stromal tumors - Menge, Franka; Jakob, Jens; Kasper, Bernd; Smakic, Armand; Gaiser, Timo; Hohenberger, Peter (Visceral medicine, 2018)
Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal neoplasms of the gastrointestinal tract. They constitute 1-2% of all gastrointestinal neoplasms but are the most common subtype of soft tissue sarcomas, accounting for 20-25%. In the late 1990s, GISTs were more and more recognized as a particular tumor entity. The tumors are supposed to originate from the interstitial pacemaker cells of Cajal. They are usually well circumscribed and can be located in every part of the tubular gastrointestinal tract. Most often GISTs occur in the stomach, followed by the small bowel and colon/rectum. In contrast to epithelial tumors, GISTs grow transmurally and submucosal. GISTs can be found with highly variable growth features including tumors with intraluminal, intra- or transmural, and pedunculated appearance. Here we describe the most common clinical presentation of GISTs on the basis of our 809 patients managed from 2004 to 2017. The median age of our patients was 59 years and the average size of GIST was 75 mm (range: 4 mm to 35 cm). The clinical presentation is very heterogeneous, depending on tumor site, size, and growth pattern. GISTs of the stomach is the group with the lowest rate of acute or emergency symptoms with 31%, followed by GISTs of the duodenum with 42%, whereas GISTs of the small bowel show acute symptoms in more than 50% of the cases and have an emergency surgery rate of almost 15%. Many patients are diagnosed accidentally, through screening examinations, or with latent, unspecific symptoms.
Gesehen am 31.03.2020